Impact of tissue atrophy on high-pass filtered MRI signal phase-based assessment in large-scale group-comparison studies: a simulation study - Schweser, Ferdinand; Dwyer, Michael G.; Deistung, Andreas; Reichenbach, Jürgen R.; Zivadinov, Robert (Frontiers in Physics, 2013)
The assessment of abnormal accumulation of tissue iron in the basal ganglia nuclei and in white matter plaques using the gradient echo magnetic resonance signal phase has become a research focus in many neurodegenerative diseases such as multiple sclerosis or Parkinson’s disease. A common and natural approach is to calculate the mean high-pass-filtered phase of previously delineated brain structures. Unfortunately, the interpretation of such an analysis requires caution: in this paper we demonstrate that regional gray matter atrophy, which is concomitant with many neurodegenerative diseases, may itself directly result in a phase shift seemingly indicative of increased iron concentration even without any real change in the tissue iron concentration. Although this effect is relatively small results of large-scale group comparisons may be driven by anatomical changes rather than by changes of the iron concentration.